Revolution or Modernization? Social Enterprises and the German Welfare Arrangement - Zimmer, Annette; Grabbe, Christina; Gluns, Danielle (Management international / International Management / Gestiòn Internacional, 2021)
The paper investigates the role of social enterprises in the German welfare arrangement. It asks whether social enterprises are drivers of a paradigmatic shift, revolutionizing the welfare arrangement, or whether they play a more modest role, contributing to adaptation to changed societal demands. Two case studies of social enterprises are analyzed through the theoretical lens of neo-institutionalism. Results show that the German welfare arrangement is not revolutionized by social enterprises as the predominance of established non-profit organizations persists. Social enterprises integrate themselves into the existing system by drawing on public funding and providing services similar to those of established providers.